A longitudinal study investigating change in BMI z-score in primary school-aged children and the association of child BMI z-score with parent BMI - R. Mears; R. Salway; D. Sharp; J. P. H. Shield; R. Jago (BMC, 2020)
Abstract Background This paper aims to explore change in BMI z-score through childhood and the association between parent BMI and child BMI z-score. This is important to understand for the development of effective obesity interventions. Methods Data from the longitudinal B-ProAct1v study (1837 participants) were analysed. A paired sample t-test examined changes in child BMI z-score between Year 1 and 4. Multivariable linear regression models examined the cross-sectional associations between child BMI z-score and parent BMI in Year 1 and 4. The influence of change in parental BMI between Year 1 and Year 4 on child BMI z-score in Year 4 was explored through regression analyses, adjusted for baseline BMI z-score. Results There was a strong association between child BMI z-score at Year 1 and 4. Child mean BMI z-score score increased from 0.198 to 0.330 (p = < 0.005) between these timepoints. For every unit increase in parent BMI, there was an increase in child BMI z-score of 0.047 in Year 1 (p = < 0.005) and of 0.059 in Year 4 (p = < 0.005). Parental BMI change was not significantly associated with Year 4 child BMI z-score. Conclusion The key indicator of higher child BMI at Year 4 is high BMI at Year 1. Further studies are needed to explore the impact of parental weight change on child BMI z-score and whether interventions targeted at overweight or obese parents, can improve their child's BMI z-score.